Term Interpretation in Patents and Trademarks: Refining the Vicarious Inquiry in Claim Construction - Warren, Leigh M. (Science and Technology Law Review, 2006)
The doctrine of claim construction has remained unsettled since the Federal Circuit declared it a matter of law ten years ago. Despite recent evidentiary clarification in Phillips, courts still struggle to construe claims as a purely legal matter. Skilled artisans’ interpretive contributions are crucial to accurate constructions, yet factual findings based on those contributions command no formal recognition in current doctrine. This Note proposes a limited role for skilled artisans’ interpretive input in determining the patentee’s intended meaning of a claim term. Specifically, skilled artisans’ interpretation of terms in the specification would be a matter of fact, informing judges’ construction of the claims as a matter of law overall. The new factual component would introduce evidentiary challenges, addressable by drawing on the evidentiary approach for determining trademark distinctiveness. The virtues of joint interpretation include accuracy and trial-level certainty, though its viability is questionable in light of the Supreme Court’s insistence on jury-free construction in Markman.